A novel perspective on doctoral supervision: Interaction of time, academic work, institutional policies, and lifecourse. Issue 1 (1st March 2022) - Bengtsen, Søren Smedegaard; McAlpine, Lynn
Abstract: While supervision is often characterised as a relatively private relationship, we would argue it is strongly influenced by departmental, institutional, national and global factors. It is also intertwined with other academic work and life experiences – with time playing an important role, not just as regards lifecourse but also changing institutional policies and practices. Using this embedded dynamic perspective in a longitudinal institutional case study, we examined how individual supervisory practices, embedded within life experiences and the evolving policy contexts of supervision and other academic activities, changed over time. We found that changed institutional supervision expectations and related structures influenced supervisory thinking and actions. Future research could further examine how this dynamic perspective opens horizons for understanding individual supervisor change in light of new institutional expectations.